PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 009 TANJUNG PENYEMBAL KOTA DUMAI - Sri Marliani Sri Marliani; Mahmud Alpusari Mahmud Alpusari; Munjiatun ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background research by low result the science lerning from the students Class III SDN 009Tanjung Penyembal Kota Dumai. The formulation of the problem is what the application of models lerning inkuiri can the result increasing student learning scinces in Class III SDN 009 Tanjung Penyembal Kota Dumai?. This reasearcs of the direction to in creasing result scinces learning to the students in Class III SDN 009 Tanjung Penyembal in the Kota Dumai. With appucations models learning inkuiri this action in the research in the class so much to doing two siklus based an analiys’s of data and discussion reasearch, evenly learning result the student experienced vaive is 65,89%, in the siklus one that 75,17%, and siklus two that is 80% in the aktiviti presentase the teacher at the siklus one the first meeting 41,66% category minus, in the second 58,33% category enaugh. In the two siklus the first meeting 70,83% category good, and that meeting in the second 91,66% with category very good, persentase activity students in the siklus one the first meeting 37,5% category minus, in the second meeting 66,66% with category enaugh. In the first siklus the rirst meeting 75% with category good, to be based on the researc of the result so can concluded that appucations models in the learning inkuiri can result incresing learning science the students Class III SDN 009 Tanjung Penyembal Kota Dumai. Keywords: Appucations Models Leraning Inkuiri, the Sciences Lerning Result